EVALUASI AUDIT OPERASIONAL TERHADAP PENINGKATAN KINERJA PELAYANAN PT POS INDONESIA (PERSERO) SURABAYA - Irawati, Dini; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The satisfaction and service expectation which is desired by the customer, it can simplify the post office to determine new policies which is more right on target to improve the financial benefit which can be more profitable for the unit of organization, since the customer satisfaction is one of the factors which determine the competitiveness to win the competition. Because, if the customers feel unsatisfied they will leave the post office and switch to other products or services which have been provided by other business entities. The research is conducted in PT. Pos Indonesia (Persero) in the area of Surabaya. Qualitative approach is the research procedure which generates written or spoken descriptive data from the observed people or behaviour. The result of the research shows that PT Pos Indonesia has implemented its policies and strategies on the one year short term plan which has been described in the Company Activity Plan and Budget (RKAP) which is prepared by each division. The preparation is based on the Strategic Direction of Management (ASM) which is the description of company strategy. Ideally, every initiative on Activity Plan and Budget (RKA) should refer to the long term program, strategic themes and Strategic Direction of Management (ASM) on the related years. Strategic Direction of Management (ASM) is the mediator between work program and RJPP.Keywords: The Evaluation of the implementation of Operational Audit, the Improvement of Service Performance, the financial benefit.